A new species of Astyanax from headwater streams of southern Brazil (Characiformes: Characidae) - de Lucena, Carlos A. S.; Bertaco, Vinicius A.; Berbigier, Guilherme (Zootaxa, 2013)
Astyanax pirabitira, new species, is described from the upper portion of the rio das Antas, laguna dos Patos system, and from the rio Pelotas, upper rio Uruguay drainage, Rio Grande do Sul State, Brazil. The new species belongs to the A. scabripinnis species complex and differs from its congeners by a combination of characters, viz., body depth (27.1–34.0% of standard length), narrow interorbital width (22.2–28.7% of head length), head depth (72.9–97.0% of HL), number of branched anal-fin rays (15–20), number of lateral line scales (37–40), one or two maxillary teeth, two humeral spots and absence of secondary sexual characters (bony hooks in the fins or other differences in the morphology). Comments on the endemic fish fauna of the region are presented.